2003
DOI: 10.1016/s0375-9601(03)00941-1
|View full text |Cite
|
Sign up to set email alerts
|

The Bloch vector for N-level systems

Abstract: We determine the set of the Bloch vectors for N -level systems, generalizing the familiar Bloch ball in 2-level systems. An origin of the structural difference from the Bloch ball in 2-level systems is clarified.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
542
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 437 publications
(558 citation statements)
references
References 18 publications
2
542
0
Order By: Relevance
“…To obtain a tighter upper bound by using the lowest order relaxation to (18), we found it most convenient to express (18) in terms of the real optimization variables, r A , r B are simply the coherence vectors that have been studied in the literature [53].…”
Section: Appendix C: Lowest Order Relaxation With Observables Of Fixementioning
confidence: 99%
“…To obtain a tighter upper bound by using the lowest order relaxation to (18), we found it most convenient to express (18) in terms of the real optimization variables, r A , r B are simply the coherence vectors that have been studied in the literature [53].…”
Section: Appendix C: Lowest Order Relaxation With Observables Of Fixementioning
confidence: 99%
“…[23] using the parametric form of an arbitrary d-dimensional density matrix, written in terms of the generators, G i , of S U(d) [28,[30][31][32][33], as…”
Section: Reciprocity Between Quantum Coherence and Mixednessmentioning
confidence: 99%
“…However, in dimensionality N = 3 or higher, it has been be shown that the physical constraint of positivity on the density matrix restricts the set of valid states to an irregular convex region that is a proper subset of the enclosing hypersphere. This physical region touches the surface of the enclosing hypersphere only in some places (where the fully polarized states lie) [25,26]. That is, many states within the hypersphere and on its surface are unphysical since they would create density matrices that are not positive.…”
Section: F Sskf Puritymentioning
confidence: 99%
“…Classes of cross section of the eight dimensional space in which the generalized Bloch vectors live, based on a figure by Kimura [26]. In each diagram, the shaded region represents the allowable states, while the outer circle is a cross section of the enclosing hypersphere.…”
Section: Figmentioning
confidence: 99%